Research trends in green marketing and intentions to purchase: A bibliometric analysis - Ambarita, Nita; Haniva, Respita; Butar Butar, Senita (Institute for Advanced Science, Social, and Sustainable Future, 2024)
The recent rise of environmental issues requires business units to prioritize sustainability in their systems and products, including marketing. People are increasingly aware of environmental damage and strive to preserve the environment. In this case, several companies have come up with several environmentally friendly products and services. This study aims to determine the trend of previous research from 2006 to 2023 on how green marketing influences consumers’ intention to purchase green products and make recommendations for future research directions. The research method uses descriptive bibliometric analysis. Based on the result of data retrieved from the Scopus database, 94 recent scientific articles are used in this review which are then converted into RIS format and processed with VOSviewer. The main findings of this study are: (1) The research on green marketing and the intention to purchase a green product emerged in 2011 and has experienced rapid development in the last decade; (2) the number of authors, institutions, and countries producing research in this field is still very limited; (3) research collaboration has not been significantly established; (4) the most productive journals in this field is Sustainability (Switzerland); (5) there are four common themes discussed in the literature on green marketing and intention to purchase green products over the last 17 years: the concept of green marketing; green purchasing behavior and intentions; environmental awareness and consumer behavior in relation to green products; and the influence of green marketing and behavior of consumer to purchase green products. The findings are discussed and the authors conclude by proposing possible avenues for future research.